Western Himalaya - Pangtey, Y. P. S.; Joshi, S. C.; Joshi, D. R.; Himalayan Research Group (India) (Nainital, U.P. : Gyanodaya Prakashan, 1987)
Studies on the Himalayan region covering Kashmir, Himachal Pradesh, and Uttar Pradesh.
Includes bibliographical references.
Keywords: Ecology -- Himalaya Mountains; Ecology -- India; Nature -- Effect of human beings on -- Himalaya Mountains; Nature -- Effect of human beings on -- India